The Impact of Endometriosis on Mental Health - A Literature Review of Depression and Anxiety Symptoms - Julia Woźniak; Sabina Kadłubek; Magdalena Mąka; Natalia Kapturska; Szymon Kalinowski; Kinga Cymerys; Piotr Kardaszewski; Jakub Kamiński; Dominik Sikora; Ewa Góralczyk (Journal of Education, Health and Sport)
Introduction and purpose: Endometriosis is a gynecological disease that affects about 10% of women worldwide. Women suffering from endometriosis are susceptible to mental health disorders, such as depression and anxiety. It is essential to highlight the psychological struggles of women with endometriosis in order to integrate physical and psychological care and subsequently enhance the treatment outcomes.